The shapes of the spectra of the equilibrium strategies for some non-zero two-person games on the unity square - Sūdžiūtė, D. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Д. П. Суджюте. Вид спектров равновесных стратегий некоторых неантагонистических игр двух лиц на единичном квадрате D. Sūdžiūtė. Kai kurių neantagonistinių dviejų asmenų lošimų vienetiniame kvadrate pusiausvyros strategijų spektrų pavidalai